2001
DOI: 10.1177/088307380101601209
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Developmental Disorders and GABAergic System in Patients With Inverted Duplicated Chromosome 15

Abstract: Pervasive developmental disorders are characterized by severe, pervasive impairment in several areas of development, with distorted communication skills and stereotypical behavior. Pervasive developmental disorders have a heterogeneous etiology related to brain damage, familial affective psychopathology, chromosomal abnormalities, or dysfunction of neuromodulators. Recently, it has been suggested that the GABRB3 gene, located within chromosome 15q11-13, is a candidate for pervasive developmental disorder. In i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Overlaps with the autism spectrum have been identified for children with a wide variety of genetically-based neurodevelopmental disorders including Down syndrome (26), Fragile-X syndrome (27) Angelman syndrome (28), Inverted Duplication 15 syndrome (29) and others. The study of ASD characteristics in populations with known genetic etiologies has grown in an effort to better understand the pathophysiology of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Overlaps with the autism spectrum have been identified for children with a wide variety of genetically-based neurodevelopmental disorders including Down syndrome (26), Fragile-X syndrome (27) Angelman syndrome (28), Inverted Duplication 15 syndrome (29) and others. The study of ASD characteristics in populations with known genetic etiologies has grown in an effort to better understand the pathophysiology of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…From these analyses, plasma GABA level in healthy subjects was found to be 98.6 ± 33.9 ng/mL (mean ± S.D., n = 12), which is statistically in accordance with the result reported recently by Shiah et al [6] (126.9 ± 63.8 ng/mL, mean ± S.D., n = 10). However, this number is much higher than some other literature values (12.5-18.8 ng/mL) [19][20][21]. After carefully reading these papers, we found that the measurements of plasma GABA in all of these works were carried out following an HPLC/fluorescence procedure described by Hare and Maynam [25].…”
Section: Determination Of Gaba In Human Plasma and Cerebrospinal Fluimentioning
confidence: 91%
“…However, the signal was too weak to make any quantitative analysis [14]. Although the HPLC-MS method was used for the determination of GABA in rat brain tissues, it had a detection limit of 2.5 ± 0.3 g/mL [18], Obviously, this method won't be sensitive enough for quantifying GABA in human plasma, in which the GABA level is consistently found to be below 150 ng/mL [4,6,[19][20][21], HPLC coupled to mass spectrometry (MS) has become a popular analytical technique. However, the sensitivity of an HPLC-MS combination is often lackluster compared with fluorescence detection, particularly when standard-size HPLC columns (4 mm i.d.)…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of the role of 15q11-q13 in social disability is further complicated by the identifi cation of a putative association between common alleles of the nonimprinted gene (GABRB3) and autism, although these fi ndings have not yet been convincingly replicated [ 45 ]. Finally, recent evidence points to dysregulation of gene expression in the 15q11-13 region in Angelman's syndrome, Rett syndrome, and autism [ 8 , 9 ].…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 98%